(untitled) (Journal of Universal Science Research, 2024)
This article conducts a comparative analysis of proverbs related to the concept of age in the Uzbek and English languages. Proverbs serve as cultural artifacts that reflect societal values and beliefs, offering insights into how different cultures perceive aging, wisdom, and the passage of time. Through a selection of Uzbek and English proverbs, the article explores common themes and differences in the portrayal of age in these linguistic traditions. Uzbek proverbs emphasize the reverence for elders and the tranquility associated with old age, while English proverbs highlight the acquisition of wisdom and the recognition of seniority. By examining these proverbs, the article sheds light on the diverse cultural perspectives on age and offers a deeper understanding of the universal human experience of aging across different societies.